Metastatic Cardiac Tumor from Precursor B Cell Lymphoblastic Lymphoma with a Mediastinal Mass: A Case Report of a 12-Years-Old African Girl - Nampijja, Dorah; Twalib, Aliku; Elias, Kumbakumba; Lubega, Sulaiman (International Archives of Cardiovascular Diseases, 2019)
Introduction: Cardiac involvement in metastatic tumors is not widely investigated. Commonest site of cardiac involvement is the pericardium. However, diffuse metastasis to the myocardium and endocardium is uncommon. Striated cardiac muscle, fast blood flow within the heart and unique lymphatic drainage make malignant metastasis to the heart rare. Cardiac metastasis is a late manifestation of malignancy and most of the cases are diagnosed on Post-mortem. We describe a case of metastatic Pre B-Lymphoblastic Lymphoma in a child who presented with heart failure. Case presentation: A 12-years-old girl was presented with an acute history of fever, cough and chest pain. She had associated difficulty in breathing, lower limb swelling and exercise intolerance. Examination findings were of a very ill child, afebrile, mild pallor, no jaundice, no lymphadenopathy. Had tachypnea, severe subcostal recession and bilateral reduced air entry, a tender hepatomegaly and grade III pedal edema, diminished peripheral pulses, excessive sweating, altered mental state and central cyanosis. Heart sounds were of normal intensity and had no murmurs. CT scan showed a large solid irregular infiltrative mediastinal mass encasing the superior vena cava, ascending aorta, trachea, descending aorta, right and left main bronchus and the cardiac chambers. Transthoracic echocardiograph showed normal sized heart chambers with grossly thickened myocardial tissue. She had multiple infiltrative masses in the lateral walls of the Right ventricle and left ventricle. She had a large fixed mass in the right atrium. Both parietal and visceral pericardia were thickened with thick pericardial effusion. Cytology revealed Precursor B cell Lymphoblastic lymphoma. Child was initiated on chemotherapy excluding anthracycline due to the poor systolic function. She got a recurrence and died eight months after initiation of chemotherapy. Conclusions: We report a case of a metastatic cardiac tumor from a Pre B- cell lymphoblastic lymphoma presenting with heart failure.
Keywords: Metastatic Cardiac Tumor; Lymphoma